General supply chain and healthcare supply chain specificities, as well as outpatient path management in Hungary - Kelen, Andrea; Faragó, Beatrix (Észak-magyarországi Stratégiai Füzetek, 2025)
The healthcare supply chain differs significantly from industrial supply chains due to its focus on human life and health. This necessitates time-sensitive, high-quality, and traceable logistics. It involves multiple stakeholders—manufacturers, distributors, providers, and patients—making it inherently complex. To improve efficiency and resilience, innovative solutions are required. The goal is to offer actionable strategies for a more effective, transparent, and equitable healthcare system. Emphasis is placed on digital tools to address structural issues and enhance care delivery. The study examines digital approaches such as blockchain, automation, and data-driven decision-making. Blockchain enhances traceability and authenticity, while automation improves inventory control and reduces errors. In Hungary, the system struggles with underfunding, workforce shortages, and regional disparities. Digital initiatives like EESZT aim to improve coordination, yet challenges like low digital literacy persist. The COVID-19 pandemic highlighted global supply chain vulnerabilities but also accelerated digital transformation. The study focuses on Hungary’s unique challenges, integrating theory and data to uncover inefficiencies and propose improvements. Findings confirm that modern technologies can significantly improve healthcare quality and sustainability.